Impresje o godności zwierząt na przykładzie rozwiązań prawnych Szwajcarii - Więckowska, Karolina (Zoophilologica. Polish Journal of Animal Studies, 2019)
The Federal Constitution of the Swiss Confederation does not only guarantee respect for human dignity, but it also states that dignity of living beings is to be respected and protected. This article presents the concept of the aforementioned dignity, followed by an indication of the sources of many interpretation problems which can be caused by this neologism. Furthermore, an attempt was made to answer the question, based on an analysis of the Animal Protection Act provisions, whether the recognition under the law that animals have dignity, will translate into their better treatment, guaranteeing them welfare or decent death. The article also shows the position of the Federal Court in relation to the concept of dignity based on the case of giving permission to carry out animal testing.